A policy proposal to strengthen the income redistribution function of the national pension scheme in South Korea: An analysis of South Korea's 5th National Pension Comprehensive Plan (draft) - Jeonyong Park (Economies, 2024)
In this study, we elucidate the income redistribution effects of the proposal to incorporate the Bend Points mechanism of the U.S. OASDI into the Korean National Pension Scheme (BP-KNPS Proposal) through a micro-simulation analysis using individual data from the Korean Labor and Income Panel Study (KLIPS). In addition to examining the effects of introducing the BP-KNPS Proposal into the current National Pension Scheme (NPS), we also consider the impact of this scheme being combined with the 5th National Pension Comprehensive Plan (Draft), announced by Korea's Ministry of Health and Welfare on 30 October 2023. When the BP-KNPS Proposal is introduced into the current NPS, the Mean Log Deviation (MLD) of the net transfer amount (lifetime pension benefits minus lifetime pension contributions) for regular employees decreases from 0.2022863 to 0.1929960. Similarly, the MLD for self-employed and irregular workers decreases from 0.2046127 to 0.1721433, indicating a reduction in income inequality. Furthermore, when the BP-KNPS Proposal is combined with the 5th National Pension Comprehensive Plan (Draft), the effects are mixed. The proposals to increase the pension contribution rate and adjust the rate increase speed via generation lead to a reduction in income inequality compared to the current NPS when combined with the BP-KNPS Proposal. However, the proposals to raise the pensionable age result in increased income inequality, similar to the outcomes under the current system. This finding suggests that the triple burden identified by literature review - the reduction in benefits due to disparities in contribution periods and life expectancy, and the raised pensionable age - has a greater impact on low-income participants than the inequality-reducing effects of the BP-KNPS Proposal.
Keywords: 330; bend points; 5th National Pension Comprehensive Plan (draft); income redistribution; intragenerational income redistribution; mean log deviation (MLD); South Korea